PENGARUH KINERJA PERUSAHAAN, KOMISARIS INDEPENDEN DAN KEPEMILIKAN MANAJERIAL TERHADAP PENGUNGKAPAN SUSTAINABILITY REPORTING (Studi Empiris pada Perusahaan yang Mengeluarkan Sustainability Reporting dan Terdaftar pada Bursa Efek Indonesia Periode 2014 - 2018) - Nelly Nuraeni; Darsono Darsono (Diponegoro Journal of Accounting, 2020)
This study aims to analyze and test the effect of company performance, independent commissioners, and managerial ownership on disclosure of sustainability reporting. Sustainability reporting as the dependent variable of the study was measured using 91 indicators based on GRI G4. Company performance includes company size, profitability, corporate growth leverage, the effectiveness of independent commissioners, and managerial ownership as independent variables.This study uses secondary data in the form of annual reports and sustainability reports obtained through the company's website and the Indonesia Stock Exchange (IDX). This research uses purposive sampling method. The populations of this study are all companies listed on the Indonesia Stock Exchange in 2014-2018. A total of 213 companies were selected as research samples from a total population of 2,705 companies during 2014-2018. The analytical method used in this study is a multiple linear regression analysis.The test results show that the independent commissioner has a positive and significant effect on the disclosure of sustainability reporting. Managerial Ownership and Company Size have a negative and significant effect on disclosure of sustainability reporting, while profitability, leverage, and company growth have no effect on disclosure on sustainability reporting.